Description of Convex Curves - Ligun, A. A.; Shumeiko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a description of convex curves, which enables one to reduce the problem of approximation of a convex curve by piecewise circular lines in the Hausdorff metric to the problem of approximation of 2π-periodic functions by trigonometric splines in the uniform metric. We describe certain properties of convex curves.